A simple guide to analyse data: Descriptive statistics in quantitative research - Libhaber, E (SA Heart Journal, 2025)
Statistical data analysis can be divided into two big domains: descriptive statistics and inferential statistics. The process of statistical inference in drawing conclusions about the entire population is based on the information from a sample.(1) Notably, “the inferential statistics process fails if the sample is not representative of the population”.(2) To achieve statistical inference, the first step of data analysis before hypothesis testing is descriptive statistics, which is directly linked to the research questions or the study objectives. This guide assumes that sampling and sample size were adequately considered before data analysis. The various steps involved in the analysis of descriptive data are discussed below.